Food industry quality control systems - Clute, Mark (CRC Press, 2009)
Authored by a 20-year food management specialist, Food Industry Quality Control Systems is the only single-source summary of basic quality control program requirements. With an emphasis on top-down management commitment, this book demonstrates the complete information collection process and essential program elements, including pest control, lot coding, organizational charts, specifications, supplier certification, and sanitation programs